Introduction. Perspectives on the Sovereignty (Italian Review of Legal History, 2022)
The Board of the Italian Review of Legal History meant in this issue of the review to contribute to the debate on the topic of the sovereignty, in a historical perspective or with regard to current events in Europe and outside Europe.The concept of sovereignty has been at the center of legal, political, philosophical and economic debate for centuries and few terms concerning institutions have taken on such a wide range of meanings in history. In different cultural spheres and from a variety of perspectives, the reflection on the polysemic content and on the various declinations of this concept in the diverse areas of the world, not only between past and present, but also regarding the possible frameworks that it could assume in the more or less near future, continues. In order to encourage the debate between scholars, the Board suggests, in counterpoint, two reflection schemes.